Voice Handicap Index (VHI) as Diagnostic Tools for Dysphonia Disorder: Narrative Literature Review - Ramakrishnan; Gopala Krishna (Archives of The Medicine and Case Reports, 2022)
In the diagnosis of dysphonia, assessing the patient's voice quality is personal and subjective. The diagnosis of voice abnormalities is based on history, physical examination, and supporting examinations. In determining the degree of Dysphonia disorder, we can use the voice handicap index. Voice Handicap Index (VHI) is one of the most widely used tools to measure the physical, functional, and emotional aspects of Dysphonia disorder.